2019
DOI: 10.1097/pcc.0000000000001865
|View full text |Cite
|
Sign up to set email alerts
|

Modified Lung Ultrasound Examinations in Assessment and Monitoring of Positive End-Expiratory Pressure-Induced Lung Reaeration in Young Children With Congenital Heart Disease Under General Anesthesia*

Abstract: Objectives: Lung ultrasound can reliably diagnose pulmonary atelectasis. The object of this study is to determine the most efficient region to assess changes in atelectasis in children with congenital heart disease under general anesthesia. Design: Randomized controlled trial. Setting: Operating room at university-affiliated children’s hospital. Patients: Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…Several studies have recently reported that using incremental PEEP results in improved lung aeration in ventilated patients with acute lung injury and ARDS 14,30‐32 . Our study findings also indicated that the iPEEPRM, starting from 0 cmH 2 O and increasing to 15 cmH 2 O, could significantly reduce atelectasis and improve lung aeration in children with CHD, as assessed using ultrasound scans, and was better than 5 cmH 2 O PEEP alone in reducing atelectasis 12 …”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Several studies have recently reported that using incremental PEEP results in improved lung aeration in ventilated patients with acute lung injury and ARDS 14,30‐32 . Our study findings also indicated that the iPEEPRM, starting from 0 cmH 2 O and increasing to 15 cmH 2 O, could significantly reduce atelectasis and improve lung aeration in children with CHD, as assessed using ultrasound scans, and was better than 5 cmH 2 O PEEP alone in reducing atelectasis 12 …”
Section: Discussionsupporting
confidence: 75%
“…As early as 1963, Bendixen et al 11 described the physiological rationale of a lung recruitment maneuver during anesthesia using an anesthesia bag for 15 seconds, which normalized arterial oxygenation and lung compliance for a short time. Our previous study also confirmed that 5 cmH 2 O PEEP could effectively reduce, but not eliminate, atelectasis in children with CHD assessed using lung ultrasound 12 …”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations